PENGARUH PERASAAN BAHAGIA DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU SMA NEGERI 1 WANGI-WANGI KABUPATEN WAKATOBI SULAWESI TENGGARA - Aswati, Aswati; Abbas, Bakhtiar; Ruslan, Ruslan (Jurnal Multidisipliner Bharasumba, 2023)
This study aims to determine and analyze the influence of happiness and emotional intelligence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi. The sample in this study consists of all teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi, totaling 56 individuals. This research employs multiple linear regression analysis. The results of the study indicate that: (1) Happiness and emotional intelligence have a positive and significant influence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi. (2) Happiness has a positive and significant influence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi. (3) Emotional intelligence has a positive and significant influence on the performance of teachers at State Senior High School 1 Wangi-Wangi, Wakatobi Regency, Southeast Sulawesi.